Stakeholders’ Needs and Opinions Regarding the Development of the Bachelor of Arts Program in Information Management and Digital Content, Faculty of Humanities and Social Sciences, Buriram Rajabhat University: Stakeholders’ Needs and Opinions Regarding the Development of the Bachelor of Arts Program in Information Management and Digital Content, Faculty of Humanities and Social Sciences, Buriram Rajabhat University - Promthong, Jutamas; Yingdaichom, Siriwan; Dumnern, Porntipa; Prasertsri, Jirayut; Rithisrithorn, Orawan; Saypunya , Sirorat; Channual , Keng (RATANABUTH JOURNAL, 2025)
This research aimed to examine the needs and opinions of stakeholders regarding the development of the Bachelor of Arts program in Information Management and Digital Content, Faculty of Humanities and Social Sciences, Buriram Rajabhat University. The sample group consisted of internal stakeholders: five curriculum instructors and fourteen current students; and external stakeholders: eighteen employers of graduates, eighteen alumni, three experts, and one hundred and ninety-four Grade 12 high school students. The research findings revealed stakeholders’ needs and opinions in four key dimensions: 1) Knowledge including information science management, digital content management, the application of technology in diverse contexts, the production of media suited to modern communication, and interdisciplinary integration in local contexts; 2) Skills involving practical and technological competencies such as information management, digital media production, creative analytical thinking, management, presentation, and professional use of digital tools, reflecting the demand for well-rounded digital-age workers; 3) Personal Attributes such as volunteer spirit, leadership, interpersonal skills, adaptability under pressure, and professional qualities like creativity, systematic thinking, and effective information management, with an emphasis on media and digital literacy; and 4) Ethics including honesty, public-mindedness, perseverance, punctuality, teamwork, and strong adherence to academic and professional ethics, such as avoiding plagiarism and using information legally.